Alcohol- and Cigarette-Use Related Behaviors During Quarantine and Physical Distancing Amid COVID-19 in Indonesia - Hanafi, Enjeline; Siste, Kristiana; Limawan, Albert Prabowo; Sen, Lee Thung; Christian, Hans; Murtani, Belinda Julivia; Adrian,; Siswidiani, Levina Putri; Suwartono, Christiany (Frontiers in Psychiatry, 2021)
Background: Indonesia implemented large-scale social restrictions (pembatasan social berskala besar/PSBB) to combat COVID-19 spread, which might influence addictive behaviors. The current study aimed to explore the fluctuation of substance use during the pandemic and association of physical distancing and related factors toward consumptions of alcohol and cigarettes. Method: An online survey was conducted from April 28 to June 1, 2020. Data regarding sociodemographic information, physical distancing profile, alcohol and cigarette usages, Alcohol Use Disorders Identification Test (AUDIT), Cigarette Dependence Scale (CDS), Symptom Checklist-90, and Pittsburg Sleep Quality Index were collected. A total of 4584 respondents from all 34 provinces in Indonesia completed the survey. Data were summarized descriptively and analyzed using chi-square, ANOVA, and multinomial regression on SPSS 23.0 for Windows. Results: During the COVID-19 pandemic in Indonesia, alcohol consumption was 9.50% and daily cigarette smoking was 20.3%. Around 44.5% and 47.6% of respondents reported stable alcohol consumption and cigarette consumption, respectively. The mean AUDIT score was 3.52±4.66 and the mean CDS score was 24.73±8.86. Physical distancing was not correlated to any substance use changes. Increased alcohol consumption was negatively correlated with being unmarried and positively correlated with higher PSQI score. Decreased alcohol use positively correlated with living in PSBB-implementing provinces and higher AUDIT scores, when compared to stable alcohol drinking. Increased cigarette smoking was positively correlated with being male, unmarried, and higher CDS scores. Reduced cigarette smoking was negatively correlated with living in provinces implementing PSBB, higher CDS scores, and phobic anxiety, hostility and psychoticism subscales of SCL-90. Discussion and Conclusion: The prevalence of alcohol and cigarette consumption changes showed a similar trend with other available studies in other countries. This study established that substance use was mainly sustained with a smaller proportion of respondents amplifying their substance usages. The changes were correlated with PSBB policy but not the practice of physical distancing. Psychiatry and addiction services in Indonesia should be strengthened to cope with the increased burden of psychological distress. Future studies should conduct more comparisons to determine whether the overall rising intensity of consumption was maintained post-pandemic and delineate acute psychopathologies' effect on substance use.